Preparation and Characterization of Modified Lead Zirconate Titanate Ceramics - Pratibha (My University, 2011)
This thesis is divided into five chapters. A brief review of research and development in solid state ferroelectric materials and in lead zirconate titanate in particular is discussed in chapter 1. Chapter 2 deals with methods of sample preparation by solid state route and characterization techniques used for studying physical properties and electrical (dielectric, ferroelectric and piezoelectric) properties of modified PZT. In chapter 3, structural and microstructural properties of La, Sm and Mn substituted modified PZT compositional series are discussed. In chapter 4, dielectric, ferroelectric and piezoelectric properties of La, Sm snd Mn substituted PZFNT series have been studied in detail. In chapter 5, Our work with future work recommendation is concluded. The suitability of the composition to give desired properties is highlighted which can be explored for various device applications
Keywords: Ferroelectric; Zirconate Titanate Ceramics